Characterization of the Dlx Enhancers in the Developing Mouse - Esau, Crystal (Université d'Ottawa / University of Ottawa, 2013)
The Distal-less homeobox (Dlx) genes encode homeodomain transcription factors found in all animals of the phylum Chordata. These genes are involved in early vertebrate development of limbs, sensory organs, branchial arches and the forebrain (telencephalon and diencephalon). The mouse and human genomes each have six Dlx genes organized into convergently transcribed bigene clusters (Dlx1/2, Dlx3/4 and Dlx5/6). In the forebrain, Dlx1/2 and Dlx5/6 genes play essential roles in GABAergic neuron proliferation, migration and survival. Each bigene cluster includes a short intergenic region (~3.5-16kb) harboring cis-regulatory elements (CREs) that control expression of the Dlx genes. The Dlx1/2 intergenic region harbors the I12b/I12a CREs, while Dlx5/6 includes I56i/I56ii. In determining the regulatory roles of the CREs on Dlx activity and forebrain development, I have characterized the phenotypic changes that occur in mice that have an I56i enhancer deletion. I have also characterized mice with double deletions of I56i and I12b as well as mice that harbored an I12b deletion and have a SNP in the I56i enhancer (vI56i). Mutant mice with a single targeted deletion of I56i are viable, fertile and do not show obvious developmental defects. These mice have significant decreases in Dlx5/6, Gad1/Gad2 and Evf-2 expression in the forebrain and have defects related to GABAergic neuron development. The ΔI56i mutants demonstrate a behavioral phenotype related to anxiety and learning deficits. Mice that lack the I12b enhancer and have the vI56i do not show morphological abnormalities but have severely disrupted Dlx expression. When mice are homozygous for the I56i and I12b enhancer deletion, they do not survive past post natal day 5 and exhibit a dwarfed body size. These mice look weak and seem to have limited motor ability. In characterizing mice with targeted deletions of highly conserved Dlx enhancers, we will have a better understanding of forebrain development.
Keywords: Development; Dlx genes; GABAergic neurons; Forebrain